2008
DOI: 10.1080/03008200802147746
|View full text |Cite
|
Sign up to set email alerts
|

Decorin-Mediated Effects in Cancer Cell Biology

Abstract: Decorin is a multifunctional molecule of the extracellular matrix. Among the multitude of assigned functions the most intriguing is the ability to inhibit the growth and the metastasis of a wide range of cancer cells in vitro. Decorin was established to directly interact with EGFR and erb2, inducing protracted receptor internalization, which results in attenuation of the receptor-mediated intacellular signaling and induction of apoptosis. Studies by our group of osteosarcoma cells described the first exception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Decorin is a key modulator of the tumour microenvironment [27] through interactions with EGFR and MAPK [28] pathways. Decorin also activates insulin-like growth factor-I receptor [29], attenuates Erb2 signalling [30], binds to TGF-Beta, activates Met and up-regulates p21 [31] [32]. While in most studies DCN has been found to have an antioncogenic role, others correlate DCN with increased migration of human osteosarcoma cells [33] and high expression in endothelial cells undergoing angiogenesis [34].…”
Section: Discussionmentioning
confidence: 99%
“…Decorin is a key modulator of the tumour microenvironment [27] through interactions with EGFR and MAPK [28] pathways. Decorin also activates insulin-like growth factor-I receptor [29], attenuates Erb2 signalling [30], binds to TGF-Beta, activates Met and up-regulates p21 [31] [32]. While in most studies DCN has been found to have an antioncogenic role, others correlate DCN with increased migration of human osteosarcoma cells [33] and high expression in endothelial cells undergoing angiogenesis [34].…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence suggests that decorin, as a key component of the tumor stroma, interacts with various growth factors such as EGF and TGF-β and is necessary for cell migration (34,35). Furthermore, it may regulate the action of several tyrosine-kinase receptors, including the EGFR, ERK and insulin-like growth factor receptor I (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies by us and others have shown that decorin is expressed by oral squamous cell carcinoma and osteosarcoma cells [20,21]. Osteosarcoma cells were shown to be insensitive to decorin-induced growth arrest, rather decorin seemed to be beneficial, since it was necessary for osteosarcoma cell migration [22]. …”
Section: Introductionmentioning
confidence: 99%